Hypertension: genes versus environment - Harrap, S.B. (The Lancet (British edition), 1994)
A review of the contributions of genes and environment to hypertension is offered, with special reference to the emerging genetics. Calculations of heritability are relevant only to the specific population and environment from which information is gathered.